IOT Application For Conveyor Motor Load Current And Temperature Monitoring Device for Factory Acceptance Test in Industrial Application - Rospawan, Ali; Simatupang, Joni Welman; Purnama, Irwan (Jurnal ELTIKOM : Jurnal Teknik Elektro, Teknologi Informasi dan Komputer, 2022)
In industrial application on machine manufacturer multinational company, especially on the conveyor manufacturing company, before delivering the conveyor to overseas customer, there are some regulations need to be complied to ensure the product quality is always good. The system to ensure the product quality before delivery is named by Factory Acceptance Test (FAT). The purpose of doing this is to gain the trust and satisfaction of the buyer company by ensuring the quality before delivery. To ensure the product quality, this device was designed following the customer check sheet and requirement by giving them reliable data of the load current on each line of the motor and the motor temperature. This device is consisting of WEMOS D1 mini as the main controller and an IoT device, thermocouple type K as a temperature sensor, MAX6675 as the driver of the thermocouple, SCT-013-005 as a split-core current sensor, Arduino Nano as the second controller, and LCD 2004 as a real-time display. The IoT Application for Conveyor Motor Load Current and Temperature Monitoring Device is successfully created with the output is a table of data and the line chart which consists of Load current on each phase (U1, V1, W1), the motor temperature, and the limitation of each data so the user is easier to determine the commissioning result of the Factory Acceptance Test.